2014
DOI: 10.3109/14767058.2013.870551
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cerclage and type of suture material: a survey of UK consultants’ practice

Abstract: There is considerable variation in practice amongst Consultant obstetricians with regards to cervical cerclage. Although most respondents use the traditional braided suture material, a significant proportion of them were not sure what is the best suture material to use. The "gestation at delivery" rate was judged to be the most important outcome for a future study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Interestingly, patient characteristics do not consistently elicit its prescription, even for women visiting the same clinic [ 14 , 24 ]. Other studies also reported that there is significant variation in clinical practice in progesterone for PTB prevention even amongst those working in the same clinic serving women with high-risk pregnancies [ 14 , 16 18 ]. However, two surveys found that most healthcare providers would be willing to take part in hypothetical progesterone trials to further evaluate its effects on PTB prevention [ 21 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, patient characteristics do not consistently elicit its prescription, even for women visiting the same clinic [ 14 , 24 ]. Other studies also reported that there is significant variation in clinical practice in progesterone for PTB prevention even amongst those working in the same clinic serving women with high-risk pregnancies [ 14 , 16 18 ]. However, two surveys found that most healthcare providers would be willing to take part in hypothetical progesterone trials to further evaluate its effects on PTB prevention [ 21 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous cross-sectional survey [ 15 ] and two chart review studies [ 16 , 17 ] focused on the acceptability of and concerns about progesterone. We identified one healthcare provider survey on cerclage [ 18 ], but most studies have focused on counselling practices on progesterone [ 15 , 18 24 ]. The need to consider women’s preferences is important because evidence has shown that most women reported greater satisfaction with their pregnancy when they were actively involved in medical decisions [ 25 ], and satisfaction, in turn, has been linked to increased confidence in their ability to take better care of themselves and their infants [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As these reports were exclusively in cohorts in which braided suture was used for cerclage, we hypothesized the reported lack of cerclage efficacy in pregnancy post-conization, relates to the effects of ‘foreign’ material (cerclage) on the vaginal microenvironment[2325] and the immune system[33]. Braided suture is the current material of choice for the cervical cerclage despite a lack of evidence to support its preferential use [17, 21, 22]. This is the first study to reveal an advantage of using a monofilament suture in pregnancies post-conization for CIN with a shortened cervix to <25mm.…”
Section: Discussionmentioning
confidence: 99%
“…However these were studies in cohorts in whom cerclage was performed using braided suture material; a reflection of current global clinical practice. In the UK Mersilene™, a non-absorbable braided polyester suture, is used by over 80% of obstetricians in preference to a monofilament alternative such as Nylon or Prolene [21], despite a lack of evidence-base. The only study to report on the effect of suture material on cerclage efficacy compared two types of braided suture, Ethibond™ and Mersilene™, and excluded all monofilament cerclages.…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a national survey of Obstetrics and Gynaecology consultants in the UK, which confirmed variability in practice - the majority of respondents were using multifilament/braided sutures, whereas only 16.6% used monofilament non-braided sutures. Significantly, 75% of respondents stated that there was no guidance for which suture material to use within their unit [5]. We subsequently conducted a systematic review, which identified only two non-randomised studies (NRS).…”
Section: Introductionmentioning
confidence: 99%